2007
DOI: 10.14712/18059694.2017.56
|View full text |Cite
|
Sign up to set email alerts
|

Essential PTX3 Biology (not only) for Cardiologists and Cardiac Surgeons

Abstract: Summary: Inflammation has been recognized to form an integral part of the atherosclerotic process. Much consideration has been given lately to the role played in atherogenesis by C-reactive protein (CRP). Although not accepted unequivocally, CRP appears to be not only a marker, but also an active mediator of the atherosclerotic process. Pentraxin 3 (PTX3) is a newly identified acute phase reactant which shares some structural and some functional properties with CRP. On the other hand, pentraxin 3 displays uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…In contrast to CRP, which is produced mainly by hepatocytes stimulated by interleukin-6 (IL-6), research indicates that PTX3 is produced mainly in atherosclerotic plaques, dendritic cells, neutrophils, macrophages, smooth muscle cells and endothelial cells. PTX3 is released in response to damage and inflammatory stimuli, 5,6 initiating complement activation and the humoral arm of the innate immune system, 7 thus acting as an early marker of vascular inflammation. It has been found to be increased both in patients with acute myocardial infarction (AMI) 8 and unstable angina pectoris (UAP).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to CRP, which is produced mainly by hepatocytes stimulated by interleukin-6 (IL-6), research indicates that PTX3 is produced mainly in atherosclerotic plaques, dendritic cells, neutrophils, macrophages, smooth muscle cells and endothelial cells. PTX3 is released in response to damage and inflammatory stimuli, 5,6 initiating complement activation and the humoral arm of the innate immune system, 7 thus acting as an early marker of vascular inflammation. It has been found to be increased both in patients with acute myocardial infarction (AMI) 8 and unstable angina pectoris (UAP).…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, an increasing number of studies have shown that PTX3 does not cause kidney damage [ 27 ] and that an elevated plasma PTX3 concentration is likely a marker of immune inflammatory response and is a physiologic protective defense mechanism, with an anti-inflammatory and protective effect on the kidneys. Previous studies have demonstrated that PTX3 can limit inflammation, promote the repair/regeneration of damaged tissue [ 28 ], and induce and maintain immune tolerance. PTX3 binds P-selectin, which allows white blood cells to roll into the apoptotic membrane of activated microvascular endothelial cells, thereby limiting subsequent leukocyte adhesion and cross-endothelial migration.…”
Section: Discussionmentioning
confidence: 99%
“…By controlling the interaction between mature dendritic cells and apoptotic cells, PTX3 participates in the removal of apoptotic cells [ 12 , 35 ]. Under inflammatory and other conditions, PTX3 induces the activation of the classical complement pathway, specifically binding apoptotic cells and cell debris on the surface of complement component C3b/iC3b, promoting complement-mediated apoptosis and cell clearance [ 28 ]. The acceleration of cellular apoptosis in DN led to a further decrease in PTX3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The prototypic long pentraxins is pentraxin-3, a homo-octameric secreted glycoprotein (34). The human pentraxin-3 protein is composed of 42 kDa subunits (32,42) and arranged as octamers made from two tetramers held together by covalent bonds (29,43,44). In addition to the conserved C-terminal domain common to all pentraxins, pentraxin-3 contains a unique N-terminal region-specific to long pentraxins (45).…”
Section: Pentraxin-3 Protein Structurementioning
confidence: 99%
“…Through its C-terminal domain, pentraxin-3 binds to the pentraxin-3-binding domain of C1q located in its globular head region ( 61 , 84 ) and triggers the activation of the downstream cascade. However, such interaction could be weakened by other pentraxins, which may compete with pentraxin-3 to bind C1q ( 42 ). Besides, pentraxin-3 glycosylation may also reduce such interaction ( 52 ), while removal of sialic acid or complete deglycosylation of pentraxin-3 significantly enhances its binding to C1q ( 52 ).…”
Section: Pentraxin-3: Mechanism Of Actionmentioning
confidence: 99%